2017
DOI: 10.17737/tre.2017.3.2.0042
|View full text |Cite
|
Sign up to set email alerts
|

A review of regression models employed for predicting diffuse solar radiation in North-Western Africa

Abstract: The knowledge of diffuse solar radiation (Hd) is of almost importance for determining the gross primary productivity, net ecosystem, exchange of carbon dioxide, light use efficiency and changing colour of the sky. However, routine measurement of Hd is not available in most locations in North-Western Africa. During the past 36 years in order to predict Hd in the horizontal surface on hourly, daily and monthly mean basis, several regression models have been developed for numerous locations in NorthWestern Africa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…In addition to latitude, orientation, and tilt angle, the intensity of cloud cover [44] and snow accumulation [45] should also be taken into consideration when deciding on the optimal tilt angle and orientation for a PV system in order to maximize its efficiency and ensure that it continues to yield the maximum possible energy output over time. Furthermore, the results of this research provide a valuable insight into the importance of accurately assessing the local climate conditions and taking all relevant factors into consideration when deciding on the optimal tilt angle and orientation for a PV system in order to maximize its efficiency and ensure that it continues to yield the maximum possible energy output over time.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to latitude, orientation, and tilt angle, the intensity of cloud cover [44] and snow accumulation [45] should also be taken into consideration when deciding on the optimal tilt angle and orientation for a PV system in order to maximize its efficiency and ensure that it continues to yield the maximum possible energy output over time. Furthermore, the results of this research provide a valuable insight into the importance of accurately assessing the local climate conditions and taking all relevant factors into consideration when deciding on the optimal tilt angle and orientation for a PV system in order to maximize its efficiency and ensure that it continues to yield the maximum possible energy output over time.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, although Bujumbura and Yaounde reported equivalent latitudes (3.61 o N and 3.84 oN, respectively), their yearly global solar radiation registered 194.4 W/m 2 and 184.3 W/m2, respectively indicating that Bujumbura receives significantly more solar radiation than Yaounde due to the different cloud cover [45], and snow accumulation factors [46] demonstrating that these are important elements to consider when making decisions regarding PV systems in different locations. The study further showed that even in locations with similar latitudes, other local climate factors such as cloud cover and snow accumulation could significantly affect the performance of a PV system and, therefore, should be taken into consideration in order to ensure that the PV system continues to yield the maximum possible energy output over its lifetime.…”
Section: Resultsmentioning
confidence: 99%
“…This is due to the reduction in global radiation entering the surface due to the obstruction of gases and aerosols in the atmosphere. The amount of diffuse radiation is higher when the atmosphere is cloudy than when the atmosphere is cloudy or sunny (Ogbulezie et al 2017). This is because the atmosphere in a clean condition indicates that the gas and aerosol content is less than when the atmosphere is in a cloudy state.…”
Section: Global Radiation Analysis and Diffuse Radiationmentioning
confidence: 99%
“…Limited access to reliable electricity grids and transmission networks [3] hinders the widespread adoption of clean energy solutions. There is a need for capacity building [4] and knowledge transfer [5] to empower local communities and governments to effectively implement and maintain these technologies.…”
Section: Introductionmentioning
confidence: 99%